(untitled) (LACCEI, 2024)
This study deals with the evaluation of satellite precipitation from the Global Precipitation Measurement (GPM) project applied in the Huallaga River basin by means of large-scale hydrological modelling. Time step was considered daily, parameter calibration was executed by trial and error and streamflow data were considered for a single station. The results showed low performance in terms of Nash-Sutcliffe efficiency. Visual analysis of the hydrographs showed an underestimation in the streamflows calculated by the hydrologic model when compared to the observed flows at the Chazuta station. The preliminary conclusion of this modelling process indicates that the satellite precipitation from the GPM project is not yet reliable for the Huallaga River basin.